Elevating professional scepticism: An exploratory study into the impact of accountability pressure and knowledge of the superior's preferences. Issue 8 (26th August 2014) - Fei Gong, Yi; Kim, Sarah; Harding, Noel
Abstract : Purpose: – The purpose of this paper is to investigate whether accountability pressure and ignorance with regard to the preferences and views of the superior are necessary characteristics of the decision environment to effectively encourage pre-emptive self-criticism and elevate professional scepticism. Auditors continue to be called to account for a perceived lack of professional scepticism in the conduct of their audits. Pre-emptive self-criticism has been proposed as one means by which the level of professional scepticism exercised by auditors may be enhanced. Design/methodology/approach: – The role of accountability pressure and knowledge of the superior's preferences in an experimental setting has been investigated, eliciting self-assessed measures of accountability pressure and manipulating whether the superior's preferences were known or unknown. Judgements are made in the context of a preliminary analytical review setting. Findings: – It was found that greater application of pre-emptive self-criticism is associated with the presence of perceived accountability pressure, but only when the superior's preferences are not known. Research limitations/implications: – Prior research reports that the effectiveness of prompts to be self-critical is limited. Findings suggest that pre-emptive self-criticism may be more effective in elevating professional scepticism than the findings of these studies suggest, and that the absence of an effect may be the result of low levels of accountability pressure in previous research settings. The results of this study imply that future research investigating pre-emptive self-criticism as a means of elevating professional scepticism should incorporate, as is the case in actual audit environments, accountability pressure in the decision setting. Practical implications: – Qualified by the need for further research, our study guides audit firms in their efforts to meet the expectations of regulators, oversight bodies, standard setters and the public at large for an elevated level of professional scepticism. Our findings suggest that placing auditors under accountability pressure might assist audit firms in meeting these expectations. Our findings also encourage auditors to exercise caution when making their preferences known to subordinates. Originality/value: – Despite its potential to help auditors meet demands for an elevated level of professional scepticism, pre-emptive self-criticism has received very little attention in the audit literature. Moreover, the few studies that have examined pre-emptive self-criticism find that prompts to be self-critical elevate professional scepticism in only limited circumstances. We make an original contribution towards an explanation for these findings, and guide future research by showing that accountability pressure is an important characteristic of the decision environment that should be in place before attempting to elevate professional scepticism through the encouragement of pre-emptive self-criticism.